Successful Treatment of Tumor-Induced Osteomalacia by Multidisciplinary Therapy with Radiation to Intracranial Fibromyxoid Tumor - Mariangela Massaccesi; Francesco Miccichè; Mario Rigante; Gianluigi Petrone; Elisabetta Lepre; Maria Antonietta Gambacorta; Vincenzo Valentini (Case Reports in Endocrinology)
Background. Tumor-induced osteomalacia (TIO) is a rare paraneoplastic syndrome caused by protein fibroblast-growth-factor-23 (FGF-23) secreting tumors. Complete tumor resection is the current standard of care for TIO; however, some patients may develop tumor recurrence. Due to the rarity of this paraneoplastic syndrome, the role of radiotherapy is unclear. This case is worth reporting because it adds to our knowledge some insights about the potential role of radiotherapy in this rare condition. Case Presentation. After multidisciplinary consultation, in July 2015, postoperative adjuvant radiotherapy was offered to a 52-year-old man with a multiple recurrent ossifying fibromyxoid tumor in the right frontal sinus causing TIO. The patient had a history of multiple bone fractures and pain since more than 20 years. The tumor had been removed in 2003 for the first time. Subsequent endoscopic resections of the tumor had been performed for recurrences of TIO in May 2012, October 2013, and July 2015. Starting from October 2015, external beam radiotherapy was delivered with a volumetric modulated arc technique to the tumor bed with a daily dose of 2 Gy up to a total dose of 60 Gy. After five years from treatment, the patient is free from local tumor relapse, TIO progression, and radiation-induced side effects. Conclusions. Radiotherapy may provide long-term TIO remission and tumor control, thus being a treatment option in cases where surgery is unfeasible or unsuccessful.